The Impact of Anthropocentric View on Ecology: A Study of Kathmandu Valley (Global Journal of Human-Social Science, 2021)
In this article the researcher unfolds the impacts of anthropocentric view on the environment and ecology of the Kathmandu Valley The research approach adopted in this article includes the anthropocentric view that separates humans from nonhuman and nature and adversely impacts the environmental ecology The main conclusions drawn from this study about the impacts of the anthropocentric view to nature are anthropocentric view separates humans from nonhuman and nature leads to the global ecological crisis human centered perspective has caused ecological crisis in the global ecological chain human centered view through technology has disrupted the natural environment of both urban and rural parts of Nepal and it is even harmful for humans
Keywords: anthropocentric; ecology; environment; impact